Regulating Undercover Policing: Subjects, Rights and Governmentality - Murphy, Brendon (Critical criminology (Richmond, B.C.), 2020)
One of Foucault’s many unfinished projects was an analysis of the links between law, power and subjectivity. This article aims to make a contribution to Foucauldian jurisprudence by asking the question: in what ways does law construct identity? Using the regulation of undercover police investigation as an example, this article considers the intersection between three core rationalities within legal systems—rights, derogation and authorization—as critical moments in the governance of human beings, mobilized through legal architectures. Here, we find identities constructed, tested and applied in a multilateral relationship as intended and unintended consequences of the technologies of law. In this space, we not only see the mechanisms of law operating for the purpose of mobilizing power relations, but we also observe the myriad ways in which the architecture of law promoting rights operates as a system of governance that reveals rights claims as hollow, impeachable and ephemeral. The article concludes by considering rights, derogation and authorization as key components of Foucauldian jurisprudence—a distinct governmentality, where law articulates what rights are available and their associated mechanics, the mechanisms of adjudication and exception, and the formal modes of counter-conduct.